A review on recent advances and applications of fish collagen. Issue 6 (26th March 2021) - Subhan, Fazli; Hussain, Zohaib; Tauseef, Isfahan; Shehzad, Adeeb; Wahid, Fazli
Abstract: During the processing of the fishery resources, the significant portion is either discarded or used to produce low-value fish meal and oil. However, the discarded portion is the rich source of valuable proteins such as collagen, vitamins, minerals, and other bioactive compounds. Collagen is a vital protein in the living body as a component of a fibrous structural protein in the extracellular matrix, connective tissue and building block of bones, tendons, skin, hair, nails, cartilage and joints. In recent years, the use of fish collagen as an increasingly valuable biomaterial has drawn considerable attention from biomedical researchers, owing to its enhanced physicochemical properties, stability and mechanical strength, biocompatibility and biodegradability. This review focuses on summarizing the growing role of fish collagen for biomedical applications. Similarly, the recent advances in various biomedical applications of fish collagen, including wound healing, tissue engineering and regeneration, drug delivery, cell culture and other therapeutic applications, are discussed in detail. These applications signify the commercial importance of fish collagen for the fishing industry, food processors and biomedical sector.